Gender Mainstreaming in Schools, Classrooms and Textbooks: Historical Perspective - Khatri, Hikamat Bahadur (HISAN: Journal of History Association of Nepal, 2023)
This study aims to explore how the gender mainstreaming process in schools. Similarly, this study has focused on gender-related content in textbooks. The gender mainstreaming is very important for Nepalese society. So this study analyses gender mainstreaming in schools, classrooms, and textbooks. In particular, gender mainstreaming empowers women in society. Therefore government need to make a good effort to create a gender-friendly environment in schools and textbooks. So how gender mainstreaming helps gender equality is the main concerning part of this study. It is based on field data generated through interaction with the participants. This study mainly dealt with two themes: gender mainstreaming in textbooks, and gender issues in school and class.